2019
DOI: 10.33549/physiolres.934348
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Locomotion and Climbing of C57Bl/6NTac Mice in a Novel Environment

Abstract: Laboratory mice in standard laboratory cages, besides horizontal and vertical locomotor activity, spontaneously display cage-bar related activities such as cage-grid climbing. Although, grid-climbing activity is one of the major components of spontaneous home-cage behavior of mice, its exact role is not fully understood. This study aimed to describe the sex-differences in coping with novelty and in spontaneous behavior of laboratory mice concerning the cage-climbing activity in an observer-independent open fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…The sample size was calculated to have enough power to detect a difference in locomotor activity in the open field observed between young and old male mice in our previous study 25 . The numbers in each group were also consistent with previous research testing both sexes in the LABORAS 28 . Behavioral recording experiments were performed before and after four weeks of drug interventions.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…The sample size was calculated to have enough power to detect a difference in locomotor activity in the open field observed between young and old male mice in our previous study 25 . The numbers in each group were also consistent with previous research testing both sexes in the LABORAS 28 . Behavioral recording experiments were performed before and after four weeks of drug interventions.…”
Section: Methodssupporting
confidence: 87%
“…Treated mice exhibited declines in mean gait speed, and the durations of climbing and grooming, compared to control. Climbing is associated with escape attempts, coping mechanisms to captivity-induced stress, curiosity, or a repetitive motor routine to explore 28 . This shows that HDBI polypharmacy inhibited the previously reported increased exploration in control mice during the first hour in LABORAS cages 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature showed sex differences in basal 35,36 and cocaineinduced locomotor activity in rodents, with females showing increased activity. 36,37 Our data confirmed these results with female mice showing an overall increased locomotor activity at basal conditions and in response to cocaine.…”
Section: Discussionmentioning
confidence: 89%
“…This was done in order to complement a recent study from our laboratory performed on males, which explored the molecular mechanism by which cocaine experienced in a new environment changed the in vivo activity of dopaminergic neurons (Creed et al, 2016). However, previous studies reported sex-related differences in behavioral reactivity to a novel environment (Borbelyova et al, 2019) and also greater tonic activity of VTA dopamine neurons in females than in males (Calipari et al, 2017). To determine if our findings can be generalized to both sexes or if there is a sex-dependent response to novelty, these experiments would need to be repeated in both sexes.…”
Section: Limitations Of the Studymentioning
confidence: 99%